A GLANCE THROUGH THE LENS OF SENIOR TEACHERS’ IMPEDIMENTS AND SUCCESSES IN ONLINE TEACHING: A CASE IN A PROVINCE IN THE PHILIPPINES - De Jesus, Jubille Melanie; Janga, Janwin Miguel; Jimenez, Joshua; Villanueva, Jaimie; Lobo, Joseph; Celis, Michael Louie (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2023)
The education sector is a major industry badly affected by the spread of COVID-19. With the abrupt transition from traditional classrooms to online learning, several obstacles arose, particularly for more senior teachers who had less time to plan for and adjust to the new model of instruction. This study was conducted to explore the challenges and successes of senior teachers from Pampanga, Philippines, in the delivery of online learning. Banking on their wisdom and experiences, this qualitative-exploratory study is guided by Kolb’s Experiential Learning Cycle (1984) and Bandura’s Social Learning Theory (1968). In-depth interviews were conducted with eight senior teachers ranging in age from 55 to 78. Their accounts, experiences, and methods were transcribed, recorded, and classified after undergoing manual qualitative analysis. The major findings highlighted the difficulties, modifications, and countermeasures that experienced educators use when delivering online classes. These results can be used to strengthen educational institutions' ability to provide and support teachers from older ge-nerations, whose knowledge and comfort with technology are limited. Most importantly, it focused on filling the gap in the dearth of research publications that have examined the difficulties and triumphs of senior teachers in the context of the new normal in Philippine education